Sukuk value and its factor determinants in Malaysian Islamic capital market - Mohd Saad, Noriza; Yusri, Dila Sharina (Journal of Islamic, Social, Economics and Development, 2025)
Malaysian Islamic capital market is a market leader in sukuk issuance compared to other capital market in the world. Thus, the objective of the study is to investigate the relationship between sukuk value of issuance with its factor determinants since this medium term and long term debt instrument facing a challenge in reducing default risks during turbulent economic situation. This study uses secondary data. The data are gathered from year 2000 to 2023 with full completed number of observations only be considered for 2840 observations. Multivariate regression are utilized for such relationship impact between sukuk value and its independent variables. The results postulated that positive real gross domestic product (real GDP), longer years to maturity and real interest rate spreading is significant positive relationship with sukuk value issuance in Malaysian Islamic capital market, thus can attract new investor and enhances existing investor confidence and reduces credit and default risks. Inversely negative growth may signify economic instability that could affect market sentiment among stakeholder.